2000
DOI: 10.1021/bi992781q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Photolabile Derivatives of Serotonin for Chemical Kinetic Investigations of the Serotonin 5-HT3 Receptor

Abstract: A series of photolabile o-nitrobenzyl derivatives of serotonin (caged serotonin) were synthesized: the amine-linked serotonin derivatives N-(2-nitrobenzyl) serotonin (Bz-5HT) and N-(alpha-carboxy-2-nitrobenzyl) serotonin (N-CNB-5HT), and O-alpha-carboxy-2-nitrobenzyl) serotonin (O-CNB-5HT), which has the caging group attached to the phenolic OH group. All the derivatives released free serotonin when excited by 308-nm or 337-nm laser pulses. The time constant of serotonin release from N-CNB-5HT was 1. 2 ms, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 62 publications
(128 reference statements)
0
46
0
2
Order By: Relevance
“…[22] This work was extended to the caging of a diverse set of biologically active peptides, [23][24][25] coenzymes, like NADP or NAD [26] and neurotransmitters, like serotonine. [27] DNA (cytosine C5)-MTases are good targets for enzyme caging, since they contain an essential cysteine residue in their active sites. Here, we show that it is possible to block the activity of DNA MTases by up to 95 % with caging, and reactivation of the enzyme by irradiation at a wavelength that does not lead to DNA or protein damage yielded 60 % A C H T U N G T R E N N U N G recovery.…”
Section: Discussionmentioning
confidence: 99%
“…[22] This work was extended to the caging of a diverse set of biologically active peptides, [23][24][25] coenzymes, like NADP or NAD [26] and neurotransmitters, like serotonine. [27] DNA (cytosine C5)-MTases are good targets for enzyme caging, since they contain an essential cysteine residue in their active sites. Here, we show that it is possible to block the activity of DNA MTases by up to 95 % with caging, and reactivation of the enzyme by irradiation at a wavelength that does not lead to DNA or protein damage yielded 60 % A C H T U N G T R E N N U N G recovery.…”
Section: Discussionmentioning
confidence: 99%
“…18) It was reported that so-called "caged" drugs, particularly those containing photocleavable protecting groups, play important roles in the control of bioactivities. [19][20][21][22][23][24][25][26] As general (not limited to metal chelators) examples of "caged" biologically active compounds, Hoffman's group reported the design and synthesis of "caged ATP," which is an ATP molecule that is protected by a photocleavable (2-nitro) phenylethyl group, to investigate the function of the Na : K pump in human red blood cells. 19) Hess' group also reported on the use of N-nitrobenzyl serotonin, a "caged serotonin," in a kinetic study of the serotonin 5-HT 3 receptor.…”
Section: -Hydroxyquinoline (Hq)-based Compounds Have Recently Been Pmentioning
confidence: 99%
“…19) Hess' group also reported on the use of N-nitrobenzyl serotonin, a "caged serotonin," in a kinetic study of the serotonin 5-HT 3 receptor. 23) The advantage of photolabile groups has been applied to caged-metal chelators [27][28][29][30] such as ethylene glycol bis(2-aminoethyl ether)-N,N,N′,N′-tetraacetic acid (EGTA) and ethylenediaminetetraacetic acid (EDTA) analogues that are protected by o-nitrophenyl groups, and can be reactivated to form metal complexes, as reported by Kaplan. 28) Therefore, one of the strategies for suppressing the toxicity and side effects of metal chelator-based drugs such as HQ would be masking the critically important moieties with protecting groups that can be removed under specific conditions.…”
Section: -Hydroxyquinoline (Hq)-based Compounds Have Recently Been Pmentioning
confidence: 99%
“…In addition, sensitivity to 5-HT release through 2-photon excitation (2PE) is desirable for localization of release to sub-cellular levels (Bort, et al, 2013; Dore, 2005; Dore and Wilson, 2011; Warther, et al, 2010). Four caged 5-HTs are known in the literature: N -CNB-5HT, O -CNB-5HT, NPEC- N -5HT (Boahen and MacDonald, 2005; Breitinger, et al, 2000), and [Ru(bpy) 2 (5HT) 2 ] 2+ (Zayat, et al, 2006) (Figure 1). Hess and co-workers synthesized N -CNB-5HT and O -CNB-5HT to study the kinetics of the 5-HT 3 ligand-gated ion channel (Breitinger, et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Four caged 5-HTs are known in the literature: N -CNB-5HT, O -CNB-5HT, NPEC- N -5HT (Boahen and MacDonald, 2005; Breitinger, et al, 2000), and [Ru(bpy) 2 (5HT) 2 ] 2+ (Zayat, et al, 2006) (Figure 1). Hess and co-workers synthesized N -CNB-5HT and O -CNB-5HT to study the kinetics of the 5-HT 3 ligand-gated ion channel (Breitinger, et al, 2000). The rate constant for release of 5-HT from N -CNB-5HT was too slow for that compound to be useful in the study, but O -CNB-5HT had sufficiently rapid release kinetics, albeit low photolysis quantum efficiency and molar absorptivity.…”
Section: Introductionmentioning
confidence: 99%